Interpolation methods of constants and means with quasi-power function parameters - Fan, Ming (MATHEMATICA SCANDINAVICA, 2001)
The purpose of this paper is to describe the interpolation methods of constants and means with quasi-power function parameters in the sense of Brudnyi-Krugljak’s K- and J-methods with the weighted Orlicz space parameters. As an application, the relationship of such methods with particular parameters and the complex methods for Banach spaces of Fourier type is sharpened.